Electronic learning communities : (Information Age Publishing ( IAP ), 2003)
This book focuses on electronic learning communities created through the development and use of the Internet for instruction and training. The chapters focus on philosophies, background, reviews, technologies, systems, tools, services, strategies, development, implementation, research, and guidelines for implementers, and each illustrates the chapter theme with a detailed example of best practices.